The Effect of Board Independence, Board Size, and Ceo Duality on Jordanian Firm Performance - Jwailes, Ahmad Rajab (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Board of director characteristics plays a major role in the firms’ performance. From those characteristics, board independence, the board size, and CEO duality were found to be effective in many studies. Therefore, this particular study is an examination of the relationships between three antecedents; board independence, the board size, and CEO duality; and the firms’ performance among the Jordanian listed firms. This study is composing a predictive model of Tobin’s Q based on three BoD antecedents as the independent variables. The regression model has the board independence, board size, and CEO duality as predictors of Tobin’s Q. This article is based on quantitative methods that used regression-based analysis for secondary panel data in the context of the Amman Stock Exchange (ASE). The time span is 10 years from 2008 to 2018 and 180 firms from the non-financial sector are included. The results revealed that the three relationships in the proposed model were found to be significant with board size having the highest negative impact, followed by CEO duality the board independence and both have a positive impact. The study can explain 62.64% of Tobin’s Q variance based on three corporate governance variables that are based on the board of directors' structure. In the future, adding more corporate governance variables such as ownership structure, board meetings, and audit committees will contribute to the proposed conceptual framework.